Adapting to Challenges: The Development of Islamic Senior High Schools in Indonesia During the COVID-19 Pandemic - Hanif, Muh; Asdlori; Efendi, Arief (International Journal of Social Science and Religion (IJSSR), 2024)
COVID-19 pandemic has changed the situation and order of economic, health, and educational life and raised various new problems in the context of education. The situation of schools that are not ready to face emergencies in the form of the Covid 19 pandemic related to the lack of preparation of internet network infrastructure, online learning systems, and the readiness of educators to carry out learning exacerbates the situation of students. This study aims to reconstruct the resilience of Islamic senior high schools during the COVID-19 pandemic. This research is a qualitative study using a phenomenological approach. The selection of research subjects using a purposive sampling technique, namely the principal, vice principal for curriculum, vice principal for student affairs, teachers, and student council administrators. Data collection techniques used interviews, observation, and documentation. Data were analyzed based on the interactive analysis model developed by Miles, Huberman & Saldana (2014), namely data condensation, data display, and conclusion drawing and verification. Each component interacts with each other and forms a cycle. The results showed: that the reconstruction of the resilience of Islamic private high schools during the Covid 19 pandemic was realized through internal school strengthening, simplifying the curriculum, determining affordable learning media platforms, improving services, and synergizing with the participation of student guardians and community leaders.